2012
DOI: 10.1002/lsm.22060
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low‐level laser therapy in a rat model of intestinal ischemia–reperfusion injury

Abstract: At the dose and parameters used, low-level laser did not protect against intestinal IRI in the acute phase of injury. However, laser did provide protection against distant organ injury. Failure to observe a therapeutic response in the intestine may be due to inappropriate dosing parameters. Furthermore, the model was designed to detect the histologic response within the first 6 hours of injury, whereas the beneficial effects of laser, if they occur, may not be observed until the later phases of healing. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Several other studies have also shown that lowpower laser irradiation has a positive therapeutic effect in a number of clinical situations (Havel et al 2012)e.g., pain relief (Fonseca et al 2012), wound healing (Kirkby et al 2012), and sports medicine (Wheeland 2012). This effect occurs through a mechanism involving acceleration of cell division, increased enzyme activity, collagen production (Calatrava et al 1997), regulation of mitochondrial processes (Karu 2008;Eells et al 2004;Prusa et al 2012), increased expression of certain proteins (Ozog et al 2012), induced synthesis of cell cycle regulatory proteins (Ocanã-Quero et al 1998a) and increase ATP production (Kirkby et al 2012;Karu 2010;Gavish et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies have also shown that lowpower laser irradiation has a positive therapeutic effect in a number of clinical situations (Havel et al 2012)e.g., pain relief (Fonseca et al 2012), wound healing (Kirkby et al 2012), and sports medicine (Wheeland 2012). This effect occurs through a mechanism involving acceleration of cell division, increased enzyme activity, collagen production (Calatrava et al 1997), regulation of mitochondrial processes (Karu 2008;Eells et al 2004;Prusa et al 2012), increased expression of certain proteins (Ozog et al 2012), induced synthesis of cell cycle regulatory proteins (Ocanã-Quero et al 1998a) and increase ATP production (Kirkby et al 2012;Karu 2010;Gavish et al 2004).…”
Section: Introductionmentioning
confidence: 99%